Assessment of Finerenone Safety and Efficacy in Individuals with Type 2 Diabetes and Chronic Kidney Disease - Roshni Gat; Shivani Kashid (International Journal of Antibiotics, 2024)
Background: In this work, we provide strong evidence for the safety and efficacy of finerenone in people with type 2 diabetes and chronic kidney disease. Our goal is to improve patients' quality of life and general well-being through our research. Aim: Finerenone exhibited a significant decrease in the likelihood of renal and cardiovascular (CV) events in individuals with both type 2 diabetes and chronic kidney disease. This exploratory subgroup analysis aims to investigate the potential influence of glucagon-like peptide-1 receptor agonists (GLP-1RAs) on the therapeutic efficacy of finerenone. Material and Method: A systemic review was undertaken, during which we scrutinized 5340 cases of these patients. Result: 394 patients, or 6.9% of the 5340 patients analyzed, were given GLP-1RAs. Finerenone was linked to a decreased UACR regardless of baseline GLP-1RA use, as evidenced by a ratio of least-squares mean of 0.69. Based on the analysis, the hazard ratio for patients who did not take GLP-1RA was 0.67 (95% confidence interval 0.67, 0.72) and for patients who did use GLP-1RA, it was 0.63 (95% confidence interval 0.56, 0.70) (p value for interaction > 0.20). Crucially, at baseline, the p values for interaction (> 0.15 and > 0.51, respectively) show that the presence of GLP-1RA had no discernible effect on the efficacy of finerenone in lowering critical secondary cardiovascular outcomes or primary kidney outcomes (defined as time to kidney failure, sustained decline in estimated glomerular filtration rate ≥40% from baseline compared to the placebo). Conclusion: Finerenone demonstrated significant advantages for both renal and cardiovascular health with minimal adverse effects. In the context of chronic kidney disease linked to type 2 diabetes, finerenone may be considered as a promising therapeutic option.
Keywords: Cardiovascular outcomes; Chronic kidney disease; Finerenone; GLP-1 receptor agonists; Glomerular filtration; Type 2 Diabetes